2015
DOI: 10.1090/jams/848
|View full text |Cite
|
Sign up to set email alerts
|

Defining totality in the enumeration degrees

Abstract: We show that if A and B form a nontrivial K-pair, then there is a semi-computable set C such that A ≤e C and B ≤e C. As a consequence, we obtain a definition of the total enumeration degrees: a nonzero enumeration degree is total if and only if it is the join of a nontrivial maximal K-pair. This answers a long-standing question of Hartley Rogers, Jr. We also obtain a definition of the "c.e. in" relation for total degrees in the enumeration degrees. 2010 Mathematics Subject Classification. 03D30. Key words and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
14
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 24 publications
0
14
0
Order By: Relevance
“…Global definability in the enumeration degrees is connected to its rigidity, in the same manner that we already described for the Turing degrees (see [32]). Cai, Ganchev, Lempp, Miller and Soskova [2] extended the ideas from [14] to give an explanation of this phenomenon. They showed that the total enumeration degrees are first order definable in D e .…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…Global definability in the enumeration degrees is connected to its rigidity, in the same manner that we already described for the Turing degrees (see [32]). Cai, Ganchev, Lempp, Miller and Soskova [2] extended the ideas from [14] to give an explanation of this phenomenon. They showed that the total enumeration degrees are first order definable in D e .…”
Section: Introductionmentioning
confidence: 89%
“…This gives a strong relationship between the automorphism problems of D e and D T : the total enumeration degrees are now a definable automorphism base for the structure of the enumeration degrees, and so the rigidity of D T would implies the the rigidity of D e . Soskova and Slaman [27] used methods from [26] and the results from [2] to show another relationship: the rigidity of any local structure -the structure of the c.e. degrees, D T (≤ 0 T ), and D e (≤ 0 e ), implies the rigidity of D e .…”
Section: Introductionmentioning
confidence: 99%
“…Th 2 pNq ď 1 ThpDq, holds as well, thus proving by the Myhill Isomorphism Theorem that the two theories are computably isomorphic, and that ThpDq is as complicated as it can be. The literature here is indeed rich of classical and celebrated results, starting from Simpson [32] who showed that the theory of the Turing degrees is computably isomorphic to Th 2 pNq: see also [33]; to mention two other major reducibilities, the theory of the m-degrees ( [24]), and the theory of the enumeration degrees ( [34]: see also [6]) are also computably isomorphic to Th 2 pNq.…”
Section: Introductionmentioning
confidence: 99%
“…Question 1.1 has a long history. Already in 1977, Jockusch and Solovay [11] showed that each jump-preserving automorphism of the Turing degrees is the identity above 0 (4) . Nerode and Shore 1980 [18] showed that each automorphism (not necessarily jump-preserving) is equal to the identity on some cone {a : a ≥ b}.…”
mentioning
confidence: 99%
“…The situation for the many-one degrees D m was long known and at the other extreme the same is true for the hyperdegrees D h . Next to be settled may be the enumeration degrees D e , see [4]. For the truth-table degrees D tt some restrictions on possible automorphisms are known.…”
mentioning
confidence: 99%